2023
DOI: 10.3390/ph16070994
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Risk for Semaglutide Misuse? Focus on the Food and Drug Administration’s FDA Adverse Events Reporting System (FAERS) Pharmacovigilance Dataset

Abstract: Recent media reports commented about a possible issue of the misuse of antidiabetics related to molecules promoted as a weight-loss treatment in non-obese people. We evaluated here available pharmacovigilance misuse/abuse signals related to semaglutide, a glucagon-like peptide-1 (GLP-1) analogue, in comparison to other GLP-1 receptor agonists (albiglutide, dulaglutide, exenatide, liraglutide, lixisenatide, and tirzepatide) and the phentermine–topiramate combination. To acheieve that aim, we analyzed the Food a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
7

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 74 publications
3
11
0
7
Order By: Relevance
“…To identify the top 30 AEs with high reporting rates and robust signals, effective signals were ranked in descending order based on the number of AE reports and the lower limit of the 95% Confidence Interval (CI) for the ROR, as shown in Table 2 . Since the PRR values were equivalent to the ROR values, our signal strength analysis focused solely on comparing the ROR 95%CI lower limits ( Chiappini et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the top 30 AEs with high reporting rates and robust signals, effective signals were ranked in descending order based on the number of AE reports and the lower limit of the 95% Confidence Interval (CI) for the ROR, as shown in Table 2 . Since the PRR values were equivalent to the ROR values, our signal strength analysis focused solely on comparing the ROR 95%CI lower limits ( Chiappini et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…• Potentially serious side effects of these medications like thyroid cancer 38 • The risk of misuse by healthy nonobese people 39 • Effects on suicidality 40 • Costs for the health care systems 41 • Attempts to obtain these medications from non-licensed and unregulated agents 42 The most frequent adverse effects of GLP-1 receptor agonists are gastrointestinal symptoms such as decreased appetite, nausea, vomiting, burping, gastrointestinal pain, and constipation. 43 Pancreatitis and biliary disease may also occur.…”
Section: Side Effectsmentioning
confidence: 99%
“…47 An analysis of the FDA Adverse Events Reporting System found that there might indeed be a misuse/abuse potential of semaglutide as a higher proportion of reports were issued with regard to drug abuse, drug withdrawal syndrome, und drug use without a prescription compared with similar medications such as other GLP-1 receptor agonists or the combination of phentermine with topiramate. 39 In 2023, the European Medicines Agency started a review of suicidality associated with liraglutide and semaglutide. The review was triggered by the Icelandic Medicines Agency following reports of suicidal thoughts and self-injury in people using liraglutide and semaglutide.…”
Section: Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the increased demand for semaglutide and the possible misuse of these antidiabetics as a weight loss treatment in non-obese people have been described in the literature and by the media [ 6 , 7 , 8 ]. Almost simultaneously, reports of suicidal thoughts in people using liraglutide and semaglutide were highlighted [ 1 ].…”
Section: Introductionmentioning
confidence: 99%